The Strategy of the Tuberculosis Acceleration Team (TP2TB) in Handling Tuberculosis Cases in Children Aged 0-14 Years in Padang City - Erlangga, Ori; Sasmita, Siska (The Future of Education Journal, 2026)
This study aims to analyze the strategy of the Tuberculosis Control Acceleration Team (TP2TB) in handling tuberculosis (TB) cases in children aged 0–14 years in Padang City. This study was motivated by the increasing number of childhood TB cases in Padang City, which has become the region with the highest number of cases in West Sumatra Province over the past five years. The study used a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. Research informants consisted of the Padang City Health Office, TP2TB members, health workers, and other related parties. The research analysis used Steensen's (2014) theory on five types of organizational strategies: joint strategies, hidden strategies, false strategies, learning strategies, and realized strategies. The results of the study indicate that TP2TB has implemented various strategies through strengthening cross-sector coordination, increasing early detection, providing Tuberculosis Preventive Therapy (TPT), and educating the public about TB in children. However, the implementation of the strategy still faces several obstacles such as low public awareness, limited coordination between agencies, low TPT achievement, and a suboptimal reporting system. Efforts to address these challenges include increasing outreach, strengthening cross-sector collaboration, optimizing case monitoring, and enhancing the capacity of healthcare workers. This research is expected to provide evaluation and recommendations to support the acceleration of TB elimination in Padang City.